The adrenergic receptor antagonists propranolol and carvedilol decrease bone sarcoma cell viability and sustained carvedilol reduces clonogenic survival and increases radiosensitivity in canine osteosarcoma cells. (8th December 2019) - Duckett, Megan M.; Phung, Shee Kwan; Nguyen, Linh; Khammanivong, Ali; Dickerson, Erin; Dusenbery, Kathryn; Lawrence, Jessica
Abstract: Adrenergic receptor (AR) expression has been demonstrated at several sites of primary and metastatic tumour growth and may influence proliferation, survival, metastasis and angiogenesis. AR antagonists like propranolol and carvedilol inhibit proliferation, induce apoptosis and synergize with chemotherapy agents in some cancers. Radiation resistance is mediated in many cells by upregulation of pro‐survival pathways, which may be influenced by ARs. Studies evaluating AR antagonists combined with radiation are limited. The purpose of this study was to determine the effect of propranolol and carvedilol on viability and radiosensitivity in sarcoma cell lines. The hypothesis was that propranolol and carvedilol would increase radiosensitivity in four primary bone sarcoma cell lines. Single agent propranolol or carvedilol inhibited cell viability in all cell lines in a concentration‐dependent manner. The mean inhibitory concentrations (IC50 ) for carvedilol were approximately 4‐fold lower than propranolol and may be clinically relevant in vivo. Immunoblot analysis confirmed AR expression in both human and canine sarcoma cell lines; however, there was no correlation between baseline AR protein expression and radiosensitivity. Short duration treatment with carvedilol and propranolol did not significantly affect clonogenic survival. Prolonged exposure to propranolol and carvedilol significantly decreased the surviving fraction of canine osteosarcoma cells after 3Gy radiation. Based on our results and possible in vivo activity in dogs, further studies investigating the effects of carvedilol on sarcoma are warranted.